(untitled) (Archive of Conferences, 2020)
The article explores the role and didactic possibilities of teaching the concept of alternative energy, alternative energy sources and devices, their use in the national economy, the concept of alternative energy in the educational process using multimedia, multimedia products, multimedia technologies and multimedia tools. The analysis of the didactic possibilities of using multimedia software teaching aids, electronic textbooks, virtual laboratory stands, 3D animations and training simulators in the content of the pedagogical basis for the formation of competencies in alternative energy in students